2013
DOI: 10.1128/jvi.02396-12
|View full text |Cite
|
Sign up to set email alerts
|

Viral Proteinase Requirements for the Nucleocytoplasmic Relocalization of Cellular Splicing Factor SRp20 during Picornavirus Infections

Abstract: Infection of mammalian cells by picornaviruses results in the nucleocytoplasmic redistribution of certain host cell proteins. These viruses interfere with import-export pathways, allowing for the cytoplasmic accumulation of nuclear proteins that are then available to function in viral processes. We recently described the cytoplasmic relocalization of cellular splicing factor SRp20 during poliovirus infection. SRp20 is an important internal ribosome entry site (IRES) trans-acting factor (ITAF) for poliovirus IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 54 publications
(67 reference statements)
4
39
0
Order By: Relevance
“…2D, lanes 1, 3, and 4) (44). Cumulatively, these results are in agreement with other reports and support the conclusion that 2A pro is the viral protease responsible for proteolysis of Nup98 (32,34).…”
Section: Cleavage Of Nup98 During Human Rhinovirus Type 2 Infectionsupporting
confidence: 93%
See 2 more Smart Citations
“…2D, lanes 1, 3, and 4) (44). Cumulatively, these results are in agreement with other reports and support the conclusion that 2A pro is the viral protease responsible for proteolysis of Nup98 (32,34).…”
Section: Cleavage Of Nup98 During Human Rhinovirus Type 2 Infectionsupporting
confidence: 93%
“…pro from all three rhinovirus species targets Nup98 and Nup153 (34) and that expression of 2A pro alone is sufficient to bring about the proteolysis of these NPC proteins (32). The results presented here indicate that HRV2 and poliovirus 2A pro proteins proteolyze Nup98 at two locations, G374 and G552.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recent studies have shown the localization in the cytoplasm of infected cells of several ITAFs, as illustrated by far upstream element binding protein 1 (FBPI) (Huang et al, 2011) or hnRNP A (Lin et al, 2009b). Redistribution of SRp20 to the cytoplasm of infected cells (Fitzgerald et al, 2013;Fitzgerald and Semler, 2011) is consistent with their capacity to stimulate enterovirus 71 (EV71) or PV IRES activity (Bedard et al, 2007).…”
Section: Itafs Stimulating Ires Activitymentioning
confidence: 88%
“…Polioviruses or rhinoviruses, for example, express a proteinase enzyme that is causing the cleavage and degradation of Nup153, Nup98 and Nup62, which consequently inhibits nucleocytoplasmic transport (Belov et al, 2000) and increases the permeability of the NPC. This increased permeability promotes passive diffusion and the re-localization of host cell nuclear proteins that take part in viral replication (Meerovitch et al, 1993;McBride et al, 1996;Gustin and Sarnow, 2001;Gustin and Sarnow, 2002;Park at al., 2008;Fitzgerald et al, 2013). Inhibition of nucleocytoplasmic transport might reduce the export of host mRNAs to the cytoplasm, which in turn is reducing the competition for the translation machinery and which is promoting viral protein synthesis.…”
Section: Nup153 and Hivmentioning
confidence: 99%